Funkcionalni bilingvizem in Slovenci v Argentini in Urugvaju - Žigon, Zvone (Dve domovini, 1996)
Slovene emigration to Argentina represents a unique peculiarity in dealing with processes of acculturation, especially with regard to the organization, solidarity and intellectual ability of the emigrants, and the emotional, ideological and religious motivations for their survival as a people. Their offspring, born in Argentina, receive their primary socialisation only in Slovene, and are later exposed to secondary, "double" socialisation (both from their Slovene parents and the wider Argentinean environment). However, with the increase in the number of mixed marriages and with the "generational" distance from the time of the first settlement and the physical distance from the true Slovene social environment, the concept of language as a proof of one's nationality and in some sense even of one's political identity is diminishing.
Keywords: akulturacija; Argentina; bilingualism; dvojezičnost; narodna identiteta; Slovenci; Slovene; Slovenes; slovenski izseljenci; slovenščina; socializacija; socialization; sociolinguistics; sociolingvistika; Spanish; španščina; Urugvaj